Coal Fly Ash as a Soil Amendment for Phosphorus Adsorption in Red Clay Soils of the Loess Plateau - GAO Jiangqi; DUAN Runbin; LU Xinyu; LI Yuzhen; SUN Yao; ZHU Bingzi (Taiyuan Ligong Daxue xuebao)
[Purposes] This work has been done to deal with soil phosphorus pollution in the Loess Plateau area and similar environmentally sensitive regions and develop a technique for reusing coal fly ash. [Methods] Batch studies with coal fly ash as a soil amendment were conducted to systematically investigate the impact of dosage, pH, initial phosphorus concentration, time, and temperature on phosphorus adsorption in red clay soils with amendment of coal fly ash. [Findings] Isothermal, kinetic, and thermodynamic analyses indicated that the addition of coal fly ash significantly enhanced the maximum adsorption capacity of red clay soils for phosphorus, accelerated the adsorption reaction rate, altered the phosphorus adsorption kinetics, and enhanced the spontaneity of the adsorption process. This study provides new insights into addressing phosphorus pollution in red clay soils in the Loess Plateau area and the sustainable disposal of coal fly ash.